Us versus them : the United States, radical Islam, and the rise of the green threat - Little, Douglas, 1950- (The University of North Carolina Press, 2022)
"...[E]xamines how American presidents, policy makers, and diplomats dealt with the rise of Islamic extremism in the modern era. Focusing on White House decision-making from George H.W. Bush to Barack Obama, [the author] traces the transformation of the Cold War-era "Red Threat" into the "Green Threat" of radical Islam...Little shows how the threat posed by Islamic "others" shaped the Middle Eastern policies of both Democratic and Republican presidents. This second edition includes a new afterword that carries the story through the Trump administration and into the Biden presidency, focusing particularly on Afghanistan..." -- back cover.